IMPLEMENTATION OF PROBLEM-BASED LEARNING MODEL TO IMPROVE THEFIFTH-GRADE STUDENTS’ LEARNING OUTCOMES AT SDN GUNUNG GEDE ONTHE DATA PROCESSING LEARNING - Ratih Jaliah; Nita Karmila; Rahayu Kartika (Primary: Jurnal Pendidikan Guru Sekolah Dasar, 2023)
This paper is a Classroom Action Research (PTK) conducted collaboratively between researchers and collaborators, which aims to improve students’ learning outcomes in mathematics learning subjects on data processing learning in class VA at SDN Gunung Gede by applying the Problem-Based Learning (PBL) model. The research subjects involved 38 students, which consist of 16 male and 22 female students. Data collection techniques in the research used five instruments, namely learning implementation assessment, changes in student activity, tests or students’ learningoutcomes, interviews, and documentation. The data analysis technique used was quantitative and qualitative analyses. Based on the research results, it can be concluded that learning with the PBL model can improve students’ learning outcomes. Learning outcomes in cycle 1 were 66% of the total students who complete and increased in cycle II to 87%. While the average score results of student activity observation in cycle I were 74 and increased in cycle II to 91.4. The quality of the learning process in cycle I likewise was 78% and in cycle II increased to 96%. Thus, theimplementation of the PBL model can improve the students’ learning outcomes on mathematics learning subjects in data processing learning in class VA at Gunung Gede Elementary School in Bogor